Terapia de compresión en pacientes con linfedema de miembro superior provocado por cáncer de mama. - Auqui Rivera, Daniela Alejandra (2025)
Introduction. Lymphedema is a chronic condition characterized by the accumulation of lymphatic fluid, commonly after breast cancer treatment. May cause pain, swelling, stiffness, and affect the quality of life. Compression therapy is a non-invasive strategy, effective in reducing the volume of the affected limb, through its different modalities and therapeutic combinations. Objective. The aim of the research was to describe the effects of compression therapy in its multiple modalities in patients with lymphedema of the upper limb caused by breast cancer, in order to provide updated evidence on its therapeutic action. Methodology. This research work was documentary, descriptive, and retrospective, based on a literature search in databases such as MEDLINE, Scopus, and Web of Science, and a systematic review of randomized controlled trials, evaluated using the Physiotherapy Evidence Database (PEDro) methodological assessment scale. Results. The search allowed the consultation of 25 scientific articles, published between 2015 and 2025, that described the benefit of compression therapy for the treatment of lymphedema. Conclusion.Compression therapy, in its multiple interventions and management protocols, such as multilayer bandages, sleeves, or compression garments and adjustable compression devices combined with technology, can significantly reduce the volume of upper limb lymphedema caused by breast cancer, improving functionality and quality of life.